Crimmigrant nations: resurgent nationalism and the closing of borders - Koulish, Robert E.; Woude, Maartje Amalia Hermina van der (Fordham University Press, 2020)
Introduction : The "Problem" of Migration / Robert Koulish and Maartje van der Woude -- Insecurity Syndrome : The Challenges of Trump's Carceral State / Tony Platt -- Migration, Populism, Racism : Between "Old" Italy and "New" Europe / Dario Melossi -- The Promise of the Border : Immigration Control and Belonging in Contemporary Britain / Ana Aliverti -- The Terrorism of Everyday Crime / Juliet P. Stumpf -- The Trumping of Neoliberal Penality? : Trump's Presidency and the Rise of Nationalist Authoritarianism in the United States / Sappho Xenakis and Leonidas K. Cheliotis -- Trump v. Hawaii : Trumpeting Authoritarianism with Formalist Analysis and Sovereign Norms / Robert Koulish -- A Path toward Nowhere : The Rise of Enforcement-Based Immigration Policy / Doris Marie Provine -- Trump Doesn't Tweet Dog Whistles, He Barks with the Dogs : Crimmigration as a Racial Project through the lens of Trump's Twitter / Rashawn Ray and Simone Durham -- Mirrors of Justice? : Undocumented Immigrants in Courts in the United States and Russia / Agnieszka Kubal and Alejandro Olayo-Méndez -- Euroskepticism, Nationalism, and the Securitization of Migration in the Netherlands / Maartje van der Woude -- Sorting Out Welfare : Crimmigration Practices and Abnormal Justice in Norway / Helene O. I. Gundhus -- The Fight against Terrorism in Belgium : Crimmigration Law as a Counterterrorism Instrument? / Lana De Pelecijn and Steven De Ridder -- How Does Crimmigration Unfold in Poland? : Between Securitization Introduced to Polish Migration Policy by Its Europeanization and Polish Xenophobia / Witold Klaus -- Migration Control, Populism, and the Spectrum of Exclusion in Turkey /  Zeynep Kasli and Zeynep Yanasmayan.